(3YbhO GdLeGfs - (3eMeO Hf HgGOQ Hf YHO Gddg GdRQcTis; (3GHf NdcGf , CMeO Hf eMeO Hf EHQGgje Hf CHj HcQ GdHQecj GdGQHdj, TeS GdOjf CHh GdYHGS,J (B681 (3g` s
(3BNQgG (B:s
(3JQLeI jhSa Hf QGaY Hf Jeje GdCSOi GHf TOGO s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B220 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B59s
(3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B561 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B185 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B2018s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
(3HgG NQe s
Keywords: (3GdJGQjNs